Characterization of sodium cellulose sulphate/poly‐dimethyl‐diallyl‐ammonium chloride biological capsules for immobilized cultivation of microalgae. Issue 4 (27th June 2012) - Zeng, Xianhai; Danquah, Michael K.; Potumarthi, Ravichandra; Cao, Jia; Chen, Xiao Dong; Lu, Yinghua
Abstract BACKGROUND: Microalgae continue to be a focus of industrial bioprocess sustainability practice owing to the numerous biofuels and bioproducts that can be obtained with simultaneous environmental bioremediation applications. However, the extremely dilute nature of large volume microalgal cultures and the small particle size of single‐cell microalgae present technological and economic problems of effective dewatering, thus affecting the application of microalgae in process industries. Microalgae immobilization using biocompatible polymeric systems has proved to be an effective strategy to circumvent the heavy dewatering requirement, as this approach provides physical separation between the solid microalgal cells and the liquid medium. RESULTS: In this work, a novel microalgae immobilization carrier, sodium cellulose sulphate/poly‐dimethyl‐diallyl‐ammonium chloride (NaCS‐PDMDAAC) capsule, was synthesized and the resulting polymeric capsules were characterized using physicochemical techniques such as Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy equipped with energy dispersive X‐ray spectroscopy (SEM‐EDX) and nuclear magnetic resonance spectroscopy (NMR). Experimental results showed that the unique properties of NaCS‐PDMDAAC capsules, such as pore size, capsule size, mechanical strength, and structural and compositional homogeneity, relevant to microalgae cultivation with batch or continuous nutrient removal can be accurately controlled. CONCLUSION: These polymeric capsules find applications not only with microalgae cultivation but also for other microorganisms. © 2012 Society of Chemical Industry